Bx must be the sum of the numbers in the bracket and c must be the product. So we need to choose 2 numbers that multiply to make 3 and add to make -4.
A negative x negative = positive so
-3*-1=3
-3-1=-4
Therefore:
(x-3)(x-1)
Answer:
<h2>C</h2>
Step-by-step explanation:
using the pythagorian theorem, we know that a^2+b^2=c^2. inputting the numbers into this equation, we get
8^2+23^2=c^2
then, using our big math brains, we get 64+529=c^2
adding together the numbers, we end up with 593
just take the sqyare root of that and bada bing bada boom! you get 24.35, or 24.4, therefore the answer is C
Answer:
119
Step-by-step explanation:
Angle C= 62
So you add 62 + 57 which gives you 119
All angles must add up to 180 so you subtract 119 from 180 which gives you 61
Since angle A is 61 and a straight line angle is 180 you subtract 61 from 180 to give you angle B
180 - 61 = 119
therefore your answer is 119
Answer:
1+1=2 additive inverse 1/2
Step-by-step explanation:
hope it helps
-2
the second equation is the result of subtracting 2